Genetic contribution of retinoid‐related genes to neural tube defects. Issue 4 (19th January 2018) - Li, Huili; Zhang, Jing; Chen, Shuyuan; Wang, Fang; Zhang, Ting; Niswander, Lee
Abstract: Rare variants are considered underlying causes of complex diseases. The complex and severe group of disorders called neural tube defects (NTDs) results from failure of the neural tube to close during early embryogenesis. Neural tube closure requires the coordination of numerous signaling pathways, including the precise regulation of retinoic acid (RA) concentration, which is controlled by enzymes involved in RA synthesis and degradation. Here, we used a case–control mutation screen study to reveal rare variants in retinoid‐related genes in a Han Chinese NTD population by sequencing six genes in 355 NTD cases and 225 controls. More specific rare variants were found in exonic and upstream regions in NTD cases. The RA‐responsive genes CYP26A1, CRABP1, and ALDH1A2 harbored NTD‐specific rare variants in their upstream regions. Unexpectedly, the majority of missense variants in NTD cases were found in CYP26B1, which encodes a RA degradation enzyme, whereas no missense variants in this gene were found in controls. Functional analysis indicated that the CYP26B1 NTD variants were inefficient in the degradation of RA using assays of RA‐induced transcription and RA‐initiated neuronal differentiation. Our study supports the contribution of rare variants in RA‐related genes to the etiology of human NTDs. Abstract : Animal studies implicate retinoid related genes as being required for neural tube closure. To identify causative rare variants associated with human neural tube defects (NTDs), we sequenced genes involved in retinoid synthesis, degradation and binding in 355 NTD cases and 225 controls. NTD‐specific rare variants were found in exonic regions and upstream regions of these genes. Functional testing of NTD‐specific missense rare variants of the degradative enzyme CYP26B1 indicates loss of function mutations that disrupt downstream gene transcription and neuronal differentiation.